Pelatihan Fotografi dan Videografi melalui Handphone untuk UMKM - Yuliawan, Rahmat; Shakila, Aurora; Syah, Aurora (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2025)
This digital world has created a new economic situation. Entrepreneurs and traders do not only sell and promote their products and services through offline. However, now everything is implemented in a hybrid form (online and offline). Starting from promoting the product or service on social media, websites, to e-commerce. Digital commerce has unlimited time and space. It is inversely different from offline trade which has space and time limitations. So that in digital marketing, the presentation of products or services must be packaged properly and can convey the message and value of the product or service. Therefore, a workshop activity with the theme "Phonegraphy to Scale Up Your Business" was held at Wijaya Putra University (offline) and through zoom (online) with Dr. Rahmat Yuliawan, SE, MM, CHRM, CPM Asia as the speaker. The results of the questionnaire data and portrait of participants' work showed that photography and videography training through cell phones was effective in increasing the competitiveness of MSMEs. The participants showed improved skills in producing high-quality photos and videos. This skill improvement can be utilized by participants to improve product quality and marketing of MSMEs. Based on the results of the study, it can be concluded that photography and videography training through mobile phones is one of the effective strategies to improve the competitiveness of MSMEs.